Evidence for a temperature-induced spin-state transition of Co3+ in La2-xSrxCoO4 - Hollmann, Nils; Haverkort, Maurits W. (Arxiv, 2011)
We study the magnetic susceptibility of mixed-valent La2-xSrxCoO4 single crystals in the doping range of 0.5<= x <= 0.8 for temperatures up to 1000 K. The magnetism below room temperature is described by paramagnetic Co2+ in the high-spin state and by Co3+ in the non-magnetic low-spin state. Above room temperature, an increase in susceptibility compared to the behavior expected from Co2+ is seen, which we attribute to a spin-state transition of Co3+. The susceptibility is analyzed by comparison to full-multiplet calculations for the thermal population of the high- and intermediate-spin states of Co3+.